2018
DOI: 10.1364/ao.57.003907
|View full text |Cite
|
Sign up to set email alerts
|

High-speed focal-distance-modulated fiber-coupled confocal sensor for coordinate measuring systems

Abstract: This article presents a new robust, precise, high-frequency focal-distance-modulated confocal point sensor for probing in coordinate measuring systems (CMSs). While maintaining the known advantages of the confocal measurement principle, the sensor represents an innovative combination of a fiber-coupled confocal illumination and detection with a tuneable, acoustically driven gradient-index fluid lens for modulation of the focus distance and a novel signal processing utilizing a lock-in amplifier. The new arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…The setup consisted of a fibre-coupled confocal sensor firstly described in [67] and in its latest design, as it was applied for the investigations shown within this paper, in [68]. A thorough description of the sensor, including the theory of the signal formation based on general works on fibre-coupled confocal sensors of Gu et al [69], may be found in [70].…”
Section: Setupmentioning
confidence: 99%
“…The setup consisted of a fibre-coupled confocal sensor firstly described in [67] and in its latest design, as it was applied for the investigations shown within this paper, in [68]. A thorough description of the sensor, including the theory of the signal formation based on general works on fibre-coupled confocal sensors of Gu et al [69], may be found in [70].…”
Section: Setupmentioning
confidence: 99%
“…One of the challenges associated with dimensional metrology is to generate highly accurate 3D relative motions between sensors and measured surfaces with sub-µm resolutions. An ultra-high-speed varifocal lens has been implemented to develop a highly accurate confocal point sensor for nano-coordinate measuring systems (CMS) 102 . Combined with a signal processing method, light-information from the fast focus modulation has been used in the confocal point sensor to significantly improve accuracy and to reduce measurement uncertainty and the probing time.…”
Section: Implications Of the Ultra-high-speed Variable Focus Optics I...mentioning
confidence: 99%
“…Der optische Aufbau des Sensors wurde detailliert in [8] vorgestellt und ist in Abbildung 1 skizziert.…”
Section: Aufbau Und Umgebungsbedingungenunclassified
“…Weiterhin werden akustisch getriebene, hochfrequent modulierbare Gradientenoptiken in Mikroskopieanwendungen [10] und konfokalen Systemen genutzt [3]. Die Kombination eines fasergekoppelten, konfokalen Punktsensors mit einer solchen Gradientenoptik zur hochfrequenten Modulation der Fokusposition unter Beibehaltung aller bekannten Vorteile der Konfokaltechnik und die Signalverarbeitung, mit welcher eine annähernd lineare Kennlinie erzeugt wird, wurde in [8] vorgestellt und wird in Kapitel 2 nochmals kurz skizziert. Außerdem ließ sich durch Quotientenbildung bei der Signalverarbeitung eine von der Reflektivität der Werkstückoberfläche und von der Verkippung derselben weitestgehend unabhängige Kennlinie erreichen [4,6].…”
Section: Introductionunclassified